Undescended testis: Level of knowledge among potential referring health‐care providers. (4th May 2015) - Lim, Li Yan; Nah, Shireen A; Lakshmi, Narasimhan K; Yap, Te‐Lu; Jacobsen, Anette S; Low, Yee; Ong, Caroline CP
Abstract : Aim: Studies report that most boys with undescended testis(UDT) are referred and operated beyond the recommended age of 1 year, possibly due to lack of awareness of treatment guidelines. We investigate the level of knowledge of UDT among potential referring health‐care providers. Method: We devised a survey on the clinical features and appropriate management of UDT. Using convenience sampling, we approached health‐care professionals with regular contact with paediatric patients and final year medical students. Respondents were allowed to remain anonymous. They were categorised according to specialty and level of experience/training. Results: Of 1179 approached, 203 responded. Thirty‐six (24%) of 149 qualified doctors had never seen a case of UDT. Median score was 6 (range 1–9). There was no significant difference in scores when comparing specialty. Mean scores decreased significantly in trend according to level of experience. When questioned regarding timings of referral and orchidopexy, 24% of qualified doctors would not refer until 9 months of age, and 66% thought orchidopexy should be done after 1 year old. Half would stop examining for UDT after 2 years old. Conclusions: Inexperience with UDT and outdated knowledge may contribute to delays in referral for UDT. Many would stop examining for UDT at 2 years old, placing undue reliance on accurate physical examination in early childhood and indicating lack of awareness of the ascending testis. Community health initiatives must emphasise recent changes in guidelines for management of UDT.